THE RELATED APPLYING CONTEXT ANALYSIS OF QUALITY OF WORK LIFE TO COMPANY’S EMPLOYEE SATISFACTION BASED ON LION SUPERINDO INDONESIA COMPANY’S EMPLOYEE DISTRICT SINGOSARI OF MALANG CITY IN THE CONTEXT OF FENOMONOLOGIST - Pratama, Magisterano Dayka (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
Quality of life (QWL) defined as a strategy of workplace to support and protect worker satisfaction goes for the purpose of raising working conditions employees and organization ( lau and may, 2002 ). Superindo As one of the companies largest retail in Indonesia has various employee with different educational background between each branch.This is what it calls Superindo for more creative and dynamic in applying QWL on each branch to improve satisfaction work in every person employees.The purpose of this research to know how the links between the application of QWL, that applied by one branch of Superindo at Superindo Singosari, Malang city with satisfaction employees.Using the methodology kualitatif-fenomonologist, researchers attempt to catch phenomena arrested researchers for working there to connect with the researchers’s knowledge as university student.Researchers interviewing deeply to 5 employee of it with a view to see how the application of QWL contained in superindo singosari and how QWL has a purport links with satisfaction of employees. The result of this research explained that the interconnected of the application of QWL on satisfaction employees has presence. Futhermore this research produce the statement that leadership is one of the most important than other factors at QWL, besides work restructuring and system of repayment in applying QWLof retail business. Keywords: quality of life, work restructuring, system of repayment ,leadership, and work satisfaction.